THE EFFECTS OF HYBRID WORK MODELS ON EMPLOYEE INNOVATIVE BEHAVIOR: THE MEDIATING ROLE OF JOB AUTONOMY - You Jia Chen (PEOPLE: International Journal of Social Sciences, 2026)
With the rapid development of digital technologies and the intensification of global competition, enterprises are facing unprecedented challenges and opportunities. Advances in information technology and evolving organizational practices have enabled firms to overcome time and space constraints, prompting a rethinking of job design and employee management. This study examines how perceived job autonomy influences employees’ innovative behavior in a remote work context and investigates its mediating role. This study adopts a questionnaire survey method for data collection, targeting employees from various industries. Using purposive sampling, 124 online responses were obtained, with 117 valid questionnaires. Measures of remote work intensity, job autonomy, and innovative behavior were adapted from established, reliable scales. Structural Equation Modeling (SEM) was used for analysis. The results indicate that: (1) remote work has a significant positive effect on job autonomy, suggesting that employees in remote settings experience greater control over their work schedules and task execution; (2) remote work promotes employees’ innovative behavior through the mediating effect of job autonomy, indicating that autonomy facilitates the generation of new ideas and improvements in work processes; and (3) job autonomy plays a significant mediating role in the relationship between remote work and innovative behavior, confirming its critical function within the overall model. Overall, this study enriches the literature on remote work and employee behavior and highlights the importance of leveraging job autonomy to maximize the benefits of remote work in both research and practice.